Catalyst for preparing gamma-valerolactone through dehydrogenation of 1, 4-pentanediol and preparation method

By using Cu/PrOx-ZnO catalyst, the problems of high cost and low efficiency of the existing γ-valerolactone production process were solved, and the efficient, green and simple γ-valerolactone preparation of 1,4-pentanediol dehydrogenation reaction was achieved, with good industrial application prospects.

CN119798191AActive Publication Date: 2025-04-11山东一诺生物质材料股份有限公司 +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510002928.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The existing γ-valerolactone (GVL) production processes have problems such as high cost, many side reactions, complex product distribution and low target product yield, which is difficult to meet the market's demand for green, simple and efficient processes.

Method used

Cu/PrOx-ZnO is used as a catalyst to prepare the catalyst through ultrasonic dissolution, hydrothermal aging and calcination, and is used for the dehydrogenation reaction of 1,4-pentanediol to achieve efficient preparation of γ-valerol.

Benefits of technology

The process conditions are mild, the conversion rate is greater than 99%, the selectivity is greater than 97%, the operation is easy to control and safe, which achieves greening of the reaction, and the catalyst has good stability, which is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798191A_ABST
    Figure CN119798191A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a catalyst for catalyzing dehydrogenation of 1, 4-pentanediol to prepare gamma-valerolactone, and the catalyst is Cu / PrOx-ZnO. The method comprises the following steps: dissolving soluble salts of copper salt, zinc salt and praseodymium salt in a mixed solution of deionized water and an organic solvent, and ultrasonically dissolving; and then sequentially adding a complexing agent and a structure-directing agent, carrying out ultrasonic dissolution again, transferring into a 100ml high-pressure hydrothermal kettle, aging for 6-72 hours under the condition of 90-180 DEG C, cooling, washing, drying and roasting to obtain the nano-sheet Cu / PrOx-ZnO catalyst with a hierarchical hierarchical pore structure. According to the present invention, with the catalyst, the gamma-valerolactone preparation through the efficient catalytic conversion of the 1, 4-pentanediol in the trickle bed reactor at the temperature of 160-210 DEG C under the solvent-free condition can be achieved, the conversion rate of the 1, 4-pentanediol is greater than 99%, the selectivity of the gamma-valerolactone is greater than 97%, the catalyst has good stability, and the catalytic activity is not significantly reduced after the continuous operation for 200 h. The catalyst provided by the invention has the advantages of hierarchical hierarchical pore nanosheet structure, abundant alkaline sites and defect sites, good active metal dispersity, high activity, easy recovery, high stability and high product yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of chemical energy technology and advanced chemical raw materials, and in particular to a catalyst and a preparation method for preparing gamma-valerolactone by dehydrogenating 1,4-pentanediol. Background Art

[0002] γ-Valerolactone (GVL for short) is a colorless or light yellow liquid with the aroma of vanillin and coconut. It has a high boiling point, strong solubility, is miscible with water and ethanol, has good stability, and is safe to use. It is an excellent solvent and is widely used in the preparation of liquid fuels. At the same time, it can be used as an additive for gasoline, diesel and biodiesel. When mixed with gasoline, its anti-knock property is the same as that of ethanol. Research results show that the properties of the mixed gasoline (95 gasoline) obtained by adding 10% GVL to 90% gasoline are very similar to those of the mixed gasoline with the same volume of ethanol, and have similar octane numbers. Since GVL does not form azeotropes with water, its lower vapor pressure improves the combustion performance of the fuel. In addition, GVL is an important raw material for fine chemicals and organic chemicals, mainly used to synthesize other carbon-based chemicals and polymer materials.

[0003] In recent years, with the continuous expansion of the use of GVL, its market demand has increased significantly. The existing production of GVL is synthesized by hydrogenation of levulinic acid or levulinic esters. However, levulinic acid is an organic acid with strong acidity in the aqueous phase, which has high requirements for reaction instruments and equipment. In addition, commonly used hydrogenation catalysts often contain precious metal components. These factors have resulted in a high production cost of GVL. Recently, there have also been reports of using furfural as a raw material to prepare GVL through a one-pot process through multiple reactions such as catalytic hydrogenation, hydrolysis and hydrogenolysis. However, there are many side reactions in this process, the product distribution is complex, and the yield of the target product is low. Therefore, it is urgent to develop a new way to prepare GVL with green process, simple operation and high efficiency.

[0004] 1,4-Pentanediol is an important energy chemical and basic organic chemical raw material. The catalytic dehydrogenation of 1,4-pentanediol to produce GVL has the potential for industrial application due to its green reaction process, simple method, low reaction cost, few side reactions, and high product yield. However, it is rarely reported.

[0005] Reaction formula for preparing GVL by dehydrogenation of 1,4-pentanediol

[0006] On December 20, 2024, a search was conducted in the Chinese Patent Publication Database with "γ-valerolactone and Cu and PrO and ZnO and dehydrogenation and catalyst" as the abstract keywords, and the option of allowing synonym expansion was checked, but no relevant literature was found.

[0007] On December 20, 2024, an abstract search for "γ-valerolactone and Cu and PrO and ZnO and dehydrogenation and catalyst" was conducted on China National Knowledge Infrastructure, and no relevant literature was found.

[0008] On December 20, 2024, a search was conducted on the website of the United States Patent and Trademark Office for "Gamma valerolactone with Cu with PrO with ZnO withdehydrogenation with catalyst", and no relevant literature was found; the search URL was https: / / ppubs.uspto.gov / pubwebapp / .

[0009] On December 20, 2024, a search was conducted on the Korean Patent Office for "Gamma valerolactone and Cu and PrO and ZnO and dehydrogenation and catalyst", and no relevant literature was found; the search URL was http: / / eng.kipris.or.kr / enghome / main.jsp.

[0010] On December 20, 2024, a search was conducted on WIPO's https: / / patentscope2.wipo.int / for "Gamma valerolactone and Cu and PrO and ZnO anddehydrogenation and catalyst", and no relevant literature was found.

[0011] On December 20, 2024, a search was conducted on the Japan Patent Office website https: / / www.j-platpat.inpit.go.jp / for "Gamma valerolactone and Cu and PrO and ZnO anddehydrogenation and catalyst", but no relevant literature was found.

[0012] Completely different from the concept of this patent. Summary of the invention

[0013] Purpose of the invention: To provide a better catalyst and preparation method for dehydrogenating 1,4-pentanediol to prepare γ-valerolactone. The specific purpose can be seen in the multiple substantial technical effects in the specific implementation part.

[0014] In order to achieve the above purpose, the present invention adopts the following technical solutions:

[0015] A catalyst for preparing γ-valerolactone by dehydrogenation of 1,4-pentanediol, characterized in that the catalyst is Cu / PrO x -ZnO; wherein the mass ratio of Cu:Pr:Zn is m(Cu):m(Pr):m(Zn):=(0.07~0.52):(0.04~0.34):1.

[0016] A method for preparing a catalyst for preparing γ-valerolactone by dehydrogenation of 1,4-pentanediol, characterized in that it comprises the following steps:

[0017] Dissolve copper salt, zinc salt and praseodymium salt in a mixed solution of deionized water and an organic solvent to prepare a metal salt mixed solution, and dissolve it by ultrasonication; wherein the mass ratio of Cu:Pr:Zn is m(Cu):m(Pr):m(Zn):=(0.07-0.52):(0.04-0.34):1;

[0018] After being uniformly dissolved, add the complexing agent and the structure directing agent in sequence, and then ultrasonically dissolve for 0.5h to 1h. After being completely dissolved, stir in a water bath at 60℃ to 80℃ for 0.5h to 1h to obtain a uniformly mixed suspension;

[0019] Then the mixed suspension was transferred to a 100 ml high pressure hydrothermal autoclave and aged at 90°C to 180°C for 6h to 72h;

[0020] After cooling, the precipitate is washed 3-5 times with deionized water and ethanol by centrifugation, dried in a drying oven at 80-150°C for 8h-16h, and then calcined in a muffle furnace at 300-700°C for 3h-5h to obtain a composite metal oxide catalyst.

[0021] A further technical solution of the present invention is that the copper salt, zinc salt and praseodymium salt are selected from any one or more of the soluble salts of copper salt, zinc salt and praseodymium salt respectively; the organic solvent is any one of N,N-dimethylformamide DMF and ethanol; the complexing agent is triethanolamine, and the structure directing agent is a 2-undecyl (heptadecanyl)-1-formamideethylimidazoline hexanediamine quaternary ammonium salt gemini surfactant.

[0022] A further technical solution of the present invention is that in the metal salt mixture, the mass concentration of Cu is 1.50 g / L to 7.50 g / L, the mass concentration of Zn is 14.44 g / L to 21.60 g / L, and the mass concentration of Pr is 0.96 g / L to 4.87 g / L;

[0023] In the mixed solution of deionized water and organic solvent, the volume ratio of deionized water to organic solvent is 0.2:1 to 1:1.

[0024] The added amount of the complexing agent is 10g to 30g based on the mass of triethanolamine added to 1L of the metal salt mixture; the added amount of the structure directing agent is 4g to 16g based on the mass of the gemini surfactant added to 1L of the metal salt mixture.

[0025] A further technical solution of the present invention is that 2-undecyl (heptadecanyl)-1-formamidoethyl imidazoline hexanediamine quaternary ammonium salt Gemini surfactant is introduced as a structure directing agent in the catalyst preparation process to control the pore structure in the catalyst. In addition, the imidazoline Gemini surfactant has a special molecular structure similar to a "triblock" polymer, and the strong chemical adsorption and bonding of N atoms and O atoms in the structure to metal ions is utilized to inhibit or promote the growth of certain crystal faces, thereby effectively controlling the catalyst morphology.

[0026] In the process of catalyst preparation, a weak base complexing agent triethanolamine TEA is introduced. Based on the property that triethanolamine can be evenly hydrolyzed to release OH under hydrothermal conditions, Cu 2+ , Zn 2+ and Pr 3+ The ions are evenly complexed to form [M(OH)4] 2- Precursor and {[M(OH)4]2-TEA} ligand, M refers to Cu 2+ 、Zn 2+ , Pr 3+;

[0027] During the hydrothermal-calcination process, the catalyst is thermally decomposed into a layered multi-level porous nanosheet composite metal oxide; the catalyst has highly dispersed active Cu sites, abundant basic sites and Pr 3+ -O v -Pr 3+ Defective structures and favorable Cu-O-Pr and Cu-O-Zn interface sites; The unique synergistic effects between surface metal sites, basic sites, defective structures, and Cu-O-Zn and Cu-O-Pr interfaces help improve the efficiency of dehydrogenation of 1,4-pentanediol to prepare γ-valerolactone. The triblock polymer is composed of three different polymer segments, each with its own unique chemical and physical properties. This structural design makes the triblock polymer highly tunable and has room for optimization in performance. By adjusting the length, chemical composition, and sequence of each segment, precise control of material properties can be achieved to meet different application requirements.

[0028] A further technical solution of the present invention is that the catalyst has a specific surface area of ​​120 m 2 / g~180m 2 / g, with a multi-level pore distribution, in which pores smaller than 2nm account for 2% to 10%, pores of 2nm to 15nm account for 67% to 90%, and the rest are macropores with a diameter of 15-30nm.

[0029] A further technical solution of the present invention is that the catalyst can generate highly dispersed active Cu sites, abundant alkaline sites and Pr 3+ -O v -Pr 3+ Defect structure and favorable Cu-O-Zn and Cu-O-Pr interface sites; under the unique synergistic effect between surface metal sites, basic sites, defect structure and Cu-O-Zn and Cu-O-Pr interfaces, the efficiency of dehydrogenation of 1,4-pentanediol to prepare γ-valerolactone can be significantly improved.

[0030] A method for synthesizing γ-valerolactone, characterized in that, under solvent-free conditions, 1,4-pentanediol is dehydrogenated to prepare γ-valerolactone using a catalyst in a trickle bed reactor; the catalyst is Cu / PrO x -ZnO; wherein the mass ratio of Cu:Pr:Zn is m(Cu):m(Pr):m(Zn):=(0.07-0.52):(0.04-0.34):1;

[0031] The catalyst is in-situ reduced in a trickle bed reactor before use, the catalyst reduction pressure is 0-0.5MPa, H2 / N2 mixed atmosphere, the flow rate is 50ml / min-150ml / min, the reduction temperature is 230°C-350°C, and the reduction time is 3h-6h;

[0032] The above dehydrogenation reaction temperature is 160℃~210℃; the liquid mass space velocity of 1,4-pentanediol is 0.05h -1 ~0.25h -1 .

[0033] The catalyst for preparing γ-valerolactone by dehydrogenation of 1,4-pentanediol is used in the reaction of preparing γ-valerolactone by dehydrogenation of 1,4-pentanediol.

[0034] A method for preparing a catalyst for preparing γ-valerolactone by dehydrogenation of 1,4-pentanediol, characterized in that the preparation method is any one of Schemes 1 to 7;

[0035] Solution 1

[0036] Weigh 11.33g Cu(NO3)2·3H2O, 96.6g Zn(NO3)2·6H2O and 7.12g Pr(NO3)3·6H2O respectively and dissolve them in a mixed solution of deionized water and DMF with a volume ratio of 0.3:1 to prepare a 1L solution with a metal Cu mass concentration of 3.00g / L, a metal Zn mass concentration of 19.50g / L and a metal Pr mass concentration of 2.31g / L. The Cu / PrO mixed solution was ultrasonically dissolved; after uniform dissolution, 20g triethanolamine complexing agent and 8g SUAEIHDI structure directing agent were added in sequence, and then ultrasonically dissolved for 0.5h. After complete dissolution, the suspension was stirred in a water bath at 80°C for 1h to obtain a uniformly mixed suspension; the uniformly mixed suspension was then transferred to a 100ml high-pressure hydrothermal autoclave, aged at 110°C for 24h, and after cooling, the precipitate was centrifugally washed 3 to 5 times with deionized water and DMF, dried in a drying oven at 100°C for 10h, and then calcined in a muffle furnace at 500°C for 3h to obtain a composite metal oxide catalyst. x -ZnO is catalyst No. 1;

[0037] Solution 2

[0038] 16.99g Cu(NO3)2·3H2O, 85.07g Zn(NO3)2·6H2O and 13.46g Pr(NO3)3·6H2O were weighed and dissolved in a mixed solution of deionized water and ethanol with a volume ratio of 0.3:1 to prepare a 1L metal salt mixed solution with a metal Cu mass concentration of 4.50g / L, a metal Zn mass concentration of 17.16g / L and a metal Pr mass concentration of 4.35g / L, and ultrasonically dissolved; after uniform dissolution, 15g triethanolamine complexing agent and 8g SHAEIHDI structure directing agent, and then ultrasonically dissolved for 0.5h. After complete dissolution, stir in a water bath at 80℃ for 1h to obtain a uniformly mixed suspension; then transfer the uniformly mixed suspension to a 100ml high-pressure hydrothermal autoclave and age at 100℃ for 36h. After cooling, the precipitate is centrifugally washed 3 to 5 times with deionized water and ethanol, dried in a drying oven at 120℃ for 10h, and then calcined in a muffle furnace at 500℃ for 5h to obtain a composite metal oxide catalyst. The obtained Cu / PrO x -ZnO is catalyst No. 2;

[0039] Option 3

[0040] 14.29g CuCl2·H2O, 32.32g ZnCl2 and 10.96g PrCl3·7H2O were weighed and dissolved in a mixed solution of deionized water and DMF with a volume ratio of 0.3:1 to prepare a 1L Cu salt mixed solution with a metal Cu mass concentration of 6.00g / L, a metal Zn mass concentration of 15.41g / L and a metal Pr mass concentration of 4.14g / L, and ultrasonically dissolved; after uniform dissolution, 15g triethanolamine complexing agent and 10g SUAEIHDI structure directing agent, and then ultrasonically dissolved for 0.5h. After complete dissolution, stir in a water bath at 80℃ for 1h to obtain a uniformly mixed suspension; then transfer the uniformly mixed suspension to a 100ml high-pressure hydrothermal autoclave and age at 120℃ for 30h. After cooling, the precipitate is centrifugally washed 3 to 5 times with deionized water and DMF, dried in a drying oven at 90℃ for 12h, and then calcined in a muffle furnace at 500℃ for 4h to obtain a composite metal oxide catalyst. The obtained Cu / PrO x -ZnO is catalyst No. 3;

[0041] Option 4

[0042] 22.65g Cu(NO3)2·3H2O, 90.64g Zn(NO3)2·6H2O and 3.16g Pr(NO3)3·6H2O were weighed and dissolved in a mixed solution of deionized water and ethanol with a volume ratio of 0.5:1 to prepare a 1L Cu salt mixed solution with a metal Cu mass concentration of 6.00g / L, a metal Zn mass concentration of 18.30g / L and a metal Pr mass concentration of 1.02g / L, and ultrasonically dissolved them; after uniform dissolution, 20g triethanolamine complexing agent and 10g SUAEIHDI structure directing agent, and then ultrasonically dissolved for 0.5h. After complete dissolution, stir in a water bath at 80℃ for 1h to obtain a uniformly mixed suspension; then transfer the uniformly mixed suspension to a 100ml high-pressure hydrothermal autoclave and age at 110℃ for 36h. After cooling, the precipitate is centrifugally washed 3 to 5 times with deionized water and DMF, dried in a drying oven at 100℃ for 12h, and then calcined in a muffle furnace at 400℃ for 5h to obtain a composite metal oxide catalyst. The obtained Cu / PrO x -ZnO is catalyst No. 4;

[0043] Option 5

[0044] 22.65g Cu(NO3)2·3H2O, 76.31g Zn(NO3)2·6H2O and 12.66g Pr(NO3)3·6H2O were weighed and dissolved in a mixed solution of deionized water and ethanol with a volume ratio of 0.3:1 to prepare a 1L Cu salt mixed solution with a metal Cu mass concentration of 6.00g / L, a metal Zn mass concentration of 15.41g / L and a metal Pr mass concentration of 4.14g / L, and ultrasonically dissolved; after uniform dissolution, 20g triethanolamine complexing agent and 12g SHAEIHDI structure directing agent, and then ultrasonically dissolved for 0.5h. After complete dissolution, stir in a water bath at 80℃ for 1h to obtain a uniformly mixed suspension; then transfer the uniformly mixed suspension to a 100ml high-pressure hydrothermal autoclave and age at 120℃ for 30h. After cooling, the precipitate is centrifugally washed 3 to 5 times with deionized water and DMF, dried in a drying oven at 100℃ for 10h, and then calcined in a muffle furnace at 500℃ for 4h to obtain a composite metal oxide catalyst. The obtained Cu / PrO x -ZnO is catalyst No. 5;

[0045] Option 6

[0046] Weigh 11.33g Cu(NO3)2·3H2O, 85.87g Zn(NO3)2·6H2O and 14.24g Pr(NO3)3·6H2O respectively and dissolve them in a mixed solution of deionized water and ethanol with a volume ratio of 0.5:1 to prepare a 1L solution with a metal Cu mass concentration of 3.00g / L, a metal Zn mass concentration of 17.33g / L and a metal Pr mass concentration of 4.60g / L. The Cu / PrO mixed solution was ultrasonically dissolved; after uniform dissolution, 20g triethanolamine complexing agent and 8g SUAEIHDI structure directing agent were added in sequence, and then ultrasonically dissolved for 0.5h. After complete dissolution, the suspension was stirred in a water bath at 80°C for 1h to obtain a uniformly mixed suspension; the uniformly mixed suspension was then transferred to a 100ml high-pressure hydrothermal autoclave, aged at 110°C for 24h, and after cooling, the precipitate was centrifugally washed 3 to 5 times with deionized water and DMF, dried in a drying oven at 80°C for 10h, and then calcined in a muffle furnace at 500°C for 3h to obtain a composite metal oxide catalyst. x -ZnO is catalyst No. 6;

[0047] Option 7

[0048] 22.65g Cu(NO3)2·3H2O, 81.10g Zn(NO3)2·6H2O and 9.49g Pr(NO3)3·6H2O were weighed and dissolved in a mixed solution of deionized water and DMF with a volume ratio of 0.5:1 to prepare a 1L Cu salt mixed solution with a metal Cu mass concentration of 6.00g / L, a metal Zn mass concentration of 16.28g / L and a metal Pr mass concentration of 3.06g / L, and ultrasonically dissolved; after uniform dissolution, 18g triethanolamine complexing agent and 10g SUAEIHDI structure directing agent, and then ultrasonically dissolved for 0.5h. After complete dissolution, stir in a water bath at 80℃ for 1h to obtain a uniformly mixed suspension; then transfer the uniformly mixed suspension to a 100ml high-pressure hydrothermal autoclave and age at 100℃ for 36h. After cooling, the precipitate is centrifugally washed 3 to 5 times with deionized water and ethanol, dried in a drying oven at 110℃ for 10h, and then calcined in a muffle furnace at 500℃ for 5h to obtain a composite metal oxide catalyst. The obtained Cu / PrO x -ZnO is catalyst No. 7.

[0049] The present invention adopting the above technical solution has the following beneficial effects compared with the prior art: the catalyst prepared by the present invention has low active metal Cu content, large specific surface area, good active metal dispersion and high activity.

[0050] The catalyst prepared by the present invention generates highly dispersed active Cu sites, abundant alkaline sites and Pr 3+ -O v -Pr 3+ Defective structure and favorable Cu-O-Zn and Cu-O-Pr interface sites. The unique synergistic effect between surface metal sites, basic sites, defective structure and Cu-O-Zn and Cu-O-Pr interfaces significantly improves the efficiency of 1,4-pentanediol dehydrogenation to γ-valerolactone.

[0051] The catalytic reaction conditions are mild (temperature < 200°C). In the trickle bed, the conversion rate of 1,4-pentanediol is greater than 99%, and the selectivity of γ-valerolactone is greater than 97%. Compared with other high-temperature conditions, the operation is easy to control and has high safety, thus realizing the greenness of the reaction.

[0052] The catalyst prepared by the present invention has good stability, and its catalytic activity does not decrease significantly after continuous operation for 200 hours, and has good industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] In order to further illustrate the present invention, the following is further described in conjunction with the accompanying drawings:

[0054] Figure 1is a typical SEM of the catalyst;

[0055] Figure 2 This is a diagram proving that the catalyst has high stability;

[0056] Figure 3 The composition and structure of the catalyst are shown in Table 1;

[0057] Figure 4 The catalyst evaluation conditions and evaluation results are shown in Table 2;

[0058] Figure 5 This is the reaction formula for the dehydrogenation of 1,4-pentanediol to prepare GVL. DETAILED DESCRIPTION

[0059] The present invention will be further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0060] In view of the defects of the existing process, the present invention provides a preparation method and application of a catalyst for catalyzing the dehydrogenation of 1,4-pentanediol to prepare γ-valerolactone. The catalyst has a simple preparation process, is non-toxic and pollution-free, has the advantages of low active metal Cu content, high catalytic activity and good stability, and has good industrial application prospects.

[0061] The catalyst used in the present invention is Cu / PrO x -ZnO.

[0062] Among them, the mass ratio of Cu:Pr:Zn is m(Cu):m(Pr):m(Zn)=(0.07~0.52):(0.04~0.34):1

[0063] The catalyst of the present invention contains Cu, ZnO and PrO x The invention discloses a plurality of components. Meanwhile, a structure-directing agent 2-undecyl-1-carboxamidoethylimidazoline hexanediamine quaternary ammonium salt (SUAEIHDI, SHAEIHDI) gemini surfactant is introduced in the catalyst preparation process to control the pore structure in the catalyst. In addition, the imidazoline gemini surfactant has a special molecular structure similar to a "triblock" polymer. The strong chemical adsorption and bonding of N atoms and O atoms in the structure to metal ions can be used to inhibit or promote the growth of certain crystal faces, thereby effectively controlling the catalyst morphology. At the same time, a weak base complexing agent triethanolamine is introduced. Based on the characteristic that triethanolamine can be uniformly hydrolyzed to release OH under hydrothermal conditions, Cu can be achieved. 2+ , Zn 2+ and Pr 3+ The ions are evenly complexed to form [M(OH)4] 2- (M refers to Cu 2+ 、Zn 2+ , Pr3+ ) precursor and {[M(OH)4]2-TEA} ligand, which are thermally decomposed and converted into layered multi-level porous nanosheet composite metal oxides during the hydrothermal-calcination process. During the reduction process, the catalyst produces highly dispersed active Cu sites, abundant alkaline sites and Pr 3+ -O v -Pr 3+ Defective structure and favorable Cu-O-Pr and Cu-O-Zn interface sites. The unique synergistic effects among surface metal sites, basic sites, defective structure, and Cu-O-Pr and Cu-O-Zn interfaces contribute to the improved efficiency of dehydrogenation of 1,4-pentanediol to γ-valerolactone.

[0064] Furthermore, the specific surface area of ​​the catalyst is 120 m 2 / g~180m 2 / g, with a multi-level pore distribution, of which pores smaller than 2nm account for 2% to 10%, pores between 2nm and 15nm account for 67% to 90%, and the rest are macropores. Mesopores are conducive to the diffusion and mass transfer of reactant molecules, thereby promoting catalytic reactions kinetically.

[0065] According to another aspect of the present invention, there is provided a method for preparing the catalyst for catalyzing the dehydrogenation of 1,4-pentanediol to prepare γ-valerolactone as described above, comprising:

[0066] Dissolve copper salt, zinc salt and praseodymium salt in a mixed solution of deionized water and organic solvent to prepare a mixed solution of metal salts, and dissolve it by ultrasonication; after uniform dissolution, add complexing agent and structure directing agent in sequence, and then dissolve it by ultrasonication for 0.5h~1h. After complete dissolution, stir it in a water bath pot at 60℃~80℃ for 0.5h~1h to obtain a uniformly mixed suspension. Then transfer the uniformly mixed suspension to a 100ml high-pressure hydrothermal autoclave, age it at 90℃~180℃ for 6h~72h, and after cooling, wash the precipitate with deionized water and ethanol by centrifugation for 3~5 times, dry it in a drying oven at 80℃~150℃ for 8h~16h, and then roast it in a muffle furnace at 300℃~700℃ for 3h~5h to obtain a composite metal oxide catalyst.

[0067] The copper salt, zinc salt and praseodymium salt described in the above method are soluble salts of copper salt, zinc salt and praseodymium salt, such as Cu(NO3)2·3H2O, Zn(NO3)2·6H2O, Pr(NO3)3·6H2O, CuCl2·H2O, ZnCl2, PrCl3·7H2O, etc.

[0068] The organic solvent in the above method is any one of N,N-dimethylformamide (DMF) and ethanol.

[0069] The complexing agent in the above method is triethanolamine, the structure directing agent is a gemini surfactant which is 2-undecyl (heptadecanyl)-1-formamidoethyl imidazoline hexanediamine quaternary ammonium salt (SUAEIHDI, SHAEIHDI),

[0070] Furthermore, in the metal salt mixture, the mass concentration of Cu is 1.50 g / L to 7.50 g / L, the mass concentration of Zn is 14.44 g / L to 21.60 g / L, and the mass concentration of Pr is 0.96 g / L to 4.87 g / L.

[0071] Furthermore, in the mixed solution of deionized water and organic solvent, the volume ratio of deionized water to organic solvent is 0.2:1 to 1:1.

[0072] Furthermore, the amount of the complexing agent added is 10 g to 30 g of triethanolamine per 1 L of the metal salt mixture. The amount of the structure directing agent added is 4 g to 16 g of the gemini surfactant per 1 L of the metal salt mixture.

[0073] According to another aspect of the present invention, there is provided use of the above-mentioned catalyst for synthesizing γ-valerolactone in the reaction of preparing γ-valerolactone by dehydrogenation of 1,4-pentanediol.

[0074] The present invention also provides a method for synthesizing γ-valerolactone, wherein the Cu / PrO x -ZnO was used as catalyst to catalyze the dehydrogenation of 1,4-pentanediol to produce γ-valerolactone in a trickle bed reactor.

[0075] Furthermore, the catalyst is reduced in situ in a trickle bed reactor before use, the catalyst reduction pressure is 0-0.5MPa, H2 / N2 mixed atmosphere, the flow rate is 50ml / min-150ml / min, the reduction temperature is 230℃-350℃, and the reduction time is 3h-6h.

[0076] Furthermore, the dehydrogenation reaction temperature is 160°C to 210°C; the liquid mass space velocity of 1,4-pentanediol is 0.05h -1 ~0.25h -1 .

[0077] According to the above synthesis method, under solvent-free conditions, in a trickle bed reactor, the conversion rate of 1,4-pentanediol is greater than 99%, and the yield of the target product γ-valerolactone is greater than 97%.

[0078] The present invention is further illustrated by the following examples, but is not limited to the following examples.

[0079] Experimental Example 1

[0080] 11.33g Cu(NO3)2·3H2O, 96.6g Zn(NO3)2·6H2O and 7.12g Pr(NO3)3·6H2O were weighed respectively and dissolved in a mixed solution of deionized water and DMF with a volume ratio of 0.3:1 to prepare a 1L Cu salt mixed solution with a metal Cu mass concentration of 3.00g / L, a metal Zn mass concentration of 19.50g / L, and a metal Pr mass concentration of 2.31g / L, and ultrasonically dissolved them; after uniform dissolution, 20g triethanolamine complexing agent and 8g SUAEIHDI structure directing agent were added in sequence, and then ultrasonically dissolved for 0.5h. After complete dissolution, stir in a water bath at 80℃ for 1h to obtain a uniformly mixed suspension. Then the mixed suspension was transferred to a 100 ml high pressure hydrothermal autoclave and aged at 110 °C for 24 h. After cooling, the precipitate was washed 3 to 5 times with deionized water and DMF by centrifugation, dried in a drying oven at 100 °C for 10 h, and then calcined in a muffle furnace at 500 °C for 3 h to obtain a composite metal oxide catalyst. The obtained Cu / PrO x -ZnO is catalyst No. 1.

[0081] Example 2

[0082] 16.99g Cu(NO3)2·3H2O, 85.07g Zn(NO3)2·6H2O and 13.46g Pr(NO3)3·6H2O were weighed respectively and dissolved in a mixed solution of deionized water and ethanol with a volume ratio of 0.3:1 to prepare 1L of metal salt mixed solution with a metal Cu mass concentration of 4.50g / L, a metal Zn mass concentration of 17.16g / L, and a metal Pr mass concentration of 4.35g / L, and ultrasonically dissolved them; after uniform dissolution, 15g triethanolamine complexing agent and 8g SHAEIHDI structure directing agent were added in sequence, and then ultrasonically dissolved for 0.5h. After complete dissolution, stir in a water bath at 80°C for 1h to obtain a uniformly mixed suspension. Then the mixed suspension was transferred to a 100 ml high pressure hydrothermal autoclave and aged at 100 °C for 36 h. After cooling, the precipitate was washed 3 to 5 times with deionized water and ethanol by centrifugation, dried in a drying oven at 120 °C for 10 h, and then calcined in a muffle furnace at 500 °C for 5 h to obtain a composite metal oxide catalyst. The obtained Cu / PrO x -ZnO is catalyst No. 2.

[0083] Example 3

[0084] 14.29g CuCl2·H2O, 32.32g ZnCl2 and 10.96g PrCl3·7H2O were weighed respectively and dissolved in a mixed solution of deionized water and DMF with a volume ratio of 0.3:1 to prepare a 1L Cu salt mixed solution with a metal Cu mass concentration of 6.00g / L, a metal Zn mass concentration of 15.41g / L, and a metal Pr mass concentration of 4.14g / L, and ultrasonically dissolved them; after uniform dissolution, 15g triethanolamine complexing agent and 10g SUAEIHDI structure directing agent were added in sequence, and then ultrasonically dissolved for 0.5h. After complete dissolution, stir in a water bath at 80°C for 1h to obtain a uniformly mixed suspension. Then the mixed suspension was transferred to a 100 ml high pressure hydrothermal autoclave and aged at 120 °C for 30 h. After cooling, the precipitate was washed 3 to 5 times with deionized water and DMF by centrifugation, dried in a drying oven at 90 °C for 12 h, and then calcined in a muffle furnace at 500 °C for 4 h to obtain a composite metal oxide catalyst. The obtained Cu / PrO x -ZnO is catalyst No. 3.

[0085] Example 4

[0086] 22.65g Cu(NO3)2·3H2O, 90.64g Zn(NO3)2·6H2O and 3.16g Pr(NO3)3·6H2O were weighed respectively and dissolved in a mixed solution of deionized water and ethanol with a volume ratio of 0.5:1 to prepare a 1L Cu salt mixed solution with a metal Cu mass concentration of 6.00g / L, a metal Zn mass concentration of 18.30g / L, and a metal Pr mass concentration of 1.02g / L, and ultrasonically dissolved them; after uniform dissolution, 20g triethanolamine complexing agent and 10g SUAEIHDI structure directing agent were added in sequence, and then ultrasonically dissolved for 0.5h. After complete dissolution, stir in a water bath at 80℃ for 1h to obtain a uniformly mixed suspension. Then the mixed suspension was transferred to a 100 ml high pressure hydrothermal autoclave and aged at 110 °C for 36 h. After cooling, the precipitate was washed 3 to 5 times with deionized water and DMF by centrifugation, dried in a 100 °C drying oven for 12 h, and then calcined in a muffle furnace at 400 °C for 5 h to obtain a composite metal oxide catalyst. The obtained Cu / PrO x -ZnO is catalyst No. 4.

[0087] Example 5

[0088] 22.65g Cu(NO3)2·3H2O, 76.31g Zn(NO3)2·6H2O and 12.66g Pr(NO3)3·6H2O were weighed respectively and dissolved in a mixed solution of deionized water and ethanol with a volume ratio of 0.3:1 to prepare a 1L Cu salt mixed solution with a metal Cu mass concentration of 6.00g / L, a metal Zn mass concentration of 15.41g / L, and a metal Pr mass concentration of 4.14g / L, and ultrasonically dissolved them; after uniform dissolution, 20g triethanolamine complexing agent and 12g SHAEIHDI structure directing agent were added in sequence, and then ultrasonically dissolved for 0.5h. After complete dissolution, stir in a water bath at 80℃ for 1h to obtain a uniformly mixed suspension. Then the mixed suspension was transferred to a 100 ml high pressure hydrothermal autoclave and aged at 120 °C for 30 h. After cooling, the precipitate was washed 3 to 5 times with deionized water and DMF by centrifugation, dried in a drying oven at 100 °C for 10 h, and then calcined in a muffle furnace at 500 °C for 4 h to obtain a composite metal oxide catalyst. The obtained Cu / PrO x -ZnO is catalyst No. 5.

[0089] Example 6

[0090] 11.33g Cu(NO3)2·3H2O, 85.87g Zn(NO3)2·6H2O and 14.24g Pr(NO3)3·6H2O were weighed respectively and dissolved in a mixed solution of deionized water and ethanol with a volume ratio of 0.5:1 to prepare 1L Cu salt mixed solution with a metal Cu mass concentration of 3.00g / L, a metal Zn mass concentration of 17.33g / L, and a metal Pr mass concentration of 4.60g / L, and ultrasonically dissolved them; after uniform dissolution, 20g triethanolamine complexing agent and 8g SUAEIHDI structure directing agent were added in sequence, and ultrasonically dissolved for 0.5h. After complete dissolution, stir in a water bath at 80℃ for 1h to obtain a uniformly mixed suspension. Then the mixed suspension was transferred to a 100 ml high pressure hydrothermal autoclave and aged at 110 °C for 24 h. After cooling, the precipitate was washed 3 to 5 times with deionized water and DMF by centrifugation, dried in a drying oven at 80 °C for 10 h, and then calcined in a muffle furnace at 500 °C for 3 h to obtain a composite metal oxide catalyst. The obtained Cu / PrO x -ZnO is catalyst No. 6.

[0091] Example 7

[0092] 22.65g Cu(NO3)2·3H2O, 81.10g Zn(NO3)2·6H2O and 9.49g Pr(NO3)3·6H2O were weighed respectively and dissolved in a mixed solution of deionized water and DMF with a volume ratio of 0.5:1 to prepare a 1L Cu salt mixed solution with a metal Cu mass concentration of 6.00g / L, a metal Zn mass concentration of 16.28g / L, and a metal Pr mass concentration of 3.06g / L, and ultrasonically dissolved them; after uniform dissolution, 18g triethanolamine complexing agent and 10g SUAEIHDI structure directing agent were added in sequence, and then ultrasonically dissolved for 0.5h. After complete dissolution, stir in a water bath at 80℃ for 1h to obtain a uniformly mixed suspension. Then the mixed suspension was transferred to a 100 ml high pressure hydrothermal autoclave and aged at 100 °C for 36 h. After cooling, the precipitate was washed 3 to 5 times with deionized water and ethanol by centrifugation, dried in a drying oven at 110 °C for 10 h, and then calcined in a muffle furnace at 500 °C for 5 h to obtain a composite metal oxide catalyst. The obtained Cu / PrO x -ZnO is catalyst No. 7.

[0093] The composition, structural characteristics and morphology of catalysts 1-6 were characterized by ICP-OES, N2-physical adsorption-desorption and SEM characterization techniques. The results are listed in Table 1. The mass ratio of Cu: Pr: Zn in the catalyst is m(Cu): m(Pr): m(Zn) = (0.07-0.52): (0.04-0.34): 1. The specific surface area of ​​the catalyst is 120 m 2 / g~180m 2 / g, with a multi-level pore distribution, of which pores with a diameter of less than 2nm account for 2% to 10%, pores with a diameter of 2nm to 15nm account for 67% to 90%, and the rest are macropores. The catalyst has a hierarchical multi-level pore nanosheet structure (typical SEM images of the catalyst are shown in Figure 2). Figure 1 ).

[0094] Table 1 Composition and structure of catalyst

[0095]

[0096]

[0097] Example 8

[0098] The above catalysts 1 to 7 were used for the dehydrogenation of 1,4-pentanediol in a trickle bed reactor. x-ZnO is used as the catalyst, and under solvent-free conditions, 1,4-pentanediol is efficiently dehydrogenated to prepare γ-valerolactone. The catalyst reduction pressure is 0-0.5MPa, H2 / N2 mixed atmosphere, flow rate is 50ml / min-150ml / min, reduction temperature is 230℃-350℃, and reduction time is 3h-6h. The dehydrogenation reaction temperature is 160℃-210℃; the liquid mass space velocity of 1,4-pentanediol is 0.05h -1 ~0.25h -1 Under the reaction conditions, the conversion rate of 1,4-pentanediol was greater than 99%, and the selectivity of γ-valerolactone was greater than 97%. The results are listed in the following Table 2 Catalyst Evaluation Conditions and Evaluation Results.

[0099] Table 2 Catalyst evaluation conditions and evaluation results

[0100]

[0101]

[0102] Example 9

[0103] The catalyst No. 5 prepared above was used to catalyze the dehydrogenation reaction of 1,4-pentanediol under the conditions of No. 8. The catalyst ran stably for 200 hours (such as Figure 2 ), the catalytic activity did not decrease significantly, indicating that the catalyst has high stability.

[0104] The above experiments show that the catalyst prepared by the present invention has high activity and stability and has potential industrial application value.

[0105] In general, the present invention relates to a preparation method and application of a catalyst for catalyzing the dehydrogenation of 1,4-pentanediol to prepare γ-valerolactone, wherein the catalyst is Cu / PrO x -ZnO. The soluble salts of copper salt, zinc salt and praseodymium salt are dissolved in a mixed solution of deionized water and an organic solvent, and ultrasonically dissolved; then the complexing agent and the structure directing agent are added in sequence, and after ultrasonically dissolved again, they are transferred to a 100 ml high pressure hydrothermal autoclave, aged at 90 ℃ to 180 ℃ for 6h to 72h, cooled, washed, dried and calcined to obtain nano-sheet Cu / PrO with a hierarchical multi-level pore structure. x-ZnO catalyst. The catalyst is used to achieve efficient catalytic conversion of 1,4-pentanediol to prepare γ-valerolactone in a trickle bed reactor at 160°C to 210°C without solvent. The conversion rate of 1,4-pentanediol is greater than 99%, and the selectivity of γ-valerolactone is greater than 97%. The catalyst has good stability and its catalytic activity does not decrease significantly after continuous operation for 200 hours. The catalyst of the present invention has a hierarchical multi-level porous nanosheet structure, abundant basic sites and defect sites, good active metal dispersion, high activity, easy recovery, high stability, and high product yield.

[0106] The basic principle, main features and advantages of the present invention are shown and described above. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the protection required.

Claims

1. A catalyst for preparing γ-valerolactone by dehydrogenation of 1,4-pentanediol, characterized in that: The catalyst is Cu / PrO x -ZnO; Among them, Cu: The mass ratio of Pr:Zn is m(Cu):m(Pr):m(Zn):=(0.07~0.52):(0.04~0.34):

1.

2. A method for preparing a catalyst for preparing γ-valerolactone by dehydrogenation of 1,4-pentanediol, characterized in that: The following steps are included: Dissolve copper salt, zinc salt and praseodymium salt in a mixed solution of deionized water and an organic solvent to prepare a metal salt mixed solution, and dissolve it by ultrasonication; wherein the mass ratio of Cu:Pr:Zn is m(Cu):m(Pr):m(Zn):=(0.07-0.52):(0.04-0.34):1; After being uniformly dissolved, add the complexing agent and the structure directing agent in sequence, and then ultrasonically dissolve for 0.5h to 1h. After being completely dissolved, stir in a water bath at 60℃ to 80℃ for 0.5h to 1h to obtain a uniformly mixed suspension; Then the mixed suspension was transferred to a 100 ml high pressure hydrothermal autoclave and aged at 90°C to 180°C for 6h to 72h; After cooling, the precipitate is washed 3-5 times with deionized water and ethanol by centrifugation, dried in a drying oven at 80-150°C for 8h-16h, and then calcined in a muffle furnace at 300-700°C for 3h-5h to obtain a composite metal oxide catalyst.

3. The method for preparing a catalyst for preparing γ-valerolactone by dehydrogenation of 1,4-pentanediol as claimed in claim 2, characterized in that: The copper salt, zinc salt and praseodymium salt are selected from any one or more of the soluble salts of copper salt, zinc salt and praseodymium salt respectively; the organic solvent is any one of N,N-dimethylformamide DMF and ethanol; the complexing agent is triethanolamine, and the structure directing agent is a gemini surfactant which is 2-undecyl(heptadeca)-1-formamideethylimidazolinehexanediamine quaternary ammonium salt.

4. The method for preparing a catalyst for preparing γ-valerolactone by dehydrogenation of 1,4-pentanediol as claimed in claim 2, characterized in that: In the metal salt mixture, the mass concentration of Cu is 1.50 g / L to 7.50 g / L, the mass concentration of Zn is 14.44 g / L to 21.60 g / L, and the mass concentration of Pr is 0.96 g / L to 4.87 g / L; In the mixed solution of deionized water and organic solvent, the volume ratio of deionized water to organic solvent is 0.2:1 to 1:1; The added amount of the complexing agent is 10g to 30g based on the mass of triethanolamine added to 1L of the metal salt mixture; the added amount of the structure directing agent is 4g to 16g based on the mass of the gemini surfactant added to 1L of the metal salt mixture.

5. The method for preparing a catalyst for preparing γ-valerolactone by dehydrogenation of 1,4-pentanediol as claimed in claim 2, characterized in that: In the catalyst preparation process, 2-undecyl-1-carboxamidoethyl imidazoline hexanediamine quaternary ammonium salt Gemini surfactant is introduced as a structure-directing agent to control the pore structure in the catalyst. In addition, the imidazoline Gemini surfactant has a special molecular structure similar to a "triblock" polymer. The strong chemical adsorption and bonding of N atoms and O atoms in its structure to metal ions can inhibit or promote the growth of certain crystal faces, thereby effectively controlling the catalyst morphology. In the process of catalyst preparation, a weak base complexing agent triethanolamine TEA is introduced. Based on the property that triethanolamine can be evenly hydrolyzed to release OH under hydrothermal conditions, Cu 2+ , Zn 2+ and Pr 3+ The ions are evenly complexed to form [M(OH)4] 2- Precursor and {[M(OH)4]2-TEA} ligand, M refers to Cu 2+ 、Zn 2+ , Pr 3+; During the hydrothermal-calcination process, the catalyst is thermally decomposed into a layered multi-level porous nanosheet composite metal oxide; the catalyst has highly dispersed active Cu sites, abundant basic sites and Pr 3+ -O v -Pr 3+ Defect structure and favorable Cu-O-Pr and Cu-O-Zn interface sites; The unique synergistic effects among surface metal sites, basic sites, defect structure, and Cu-O-Zn and Cu-O-Pr interfaces help to improve the efficiency of dehydrogenation of 1,4-pentanediol to prepare γ-valerolactone.

6. The method for preparing a catalyst for preparing γ-valerolactone by dehydrogenation of 1,4-pentanediol as claimed in claim 2, characterized in that: The specific surface area of ​​the catalyst is 120 m 2 / g~180m 2 / g, with a multi-level pore distribution, in which pores smaller than 2nm account for 2% to 10%, pores of 2nm to 15nm account for 67% to 90%, and the rest are macropores with a diameter of 15-30nm.

7. The method for preparing a catalyst for preparing γ-valerolactone by dehydrogenation of 1,4-pentanediol as claimed in claim 2, characterized in that: During the reduction process, the catalyst can generate highly dispersed active Cu sites, abundant basic sites and Pr 3+ -O v -Pr 3+ Defect structure and favorable Cu-O-Zn and Cu-O-Pr interface sites; under the unique synergistic effect between surface metal sites, basic sites, defect structure and Cu-O-Zn and Cu-O-Pr interfaces, the efficiency of dehydrogenation of 1,4-pentanediol to prepare γ-valerolactone can be significantly improved.

8. A method for synthesizing γ-valerolactone, characterized in that: Under solvent-free conditions, 1,4-pentanediol is dehydrogenated to prepare γ-valerolactone in a trickle bed reactor using a catalyst; the catalyst is Cu / PrO x -ZnO; Among them, Cu: The mass ratio of Pr:Zn is m(Cu):m(Pr):m(Zn):=(0.07-0.52):(0.04-0.34):1; The catalyst is in-situ reduced in a trickle bed reactor before use, the catalyst reduction pressure is 0-0.5MPa, H2 / N2 mixed atmosphere, the flow rate is 50ml / min-150ml / min, the reduction temperature is 230°C-350°C, and the reduction time is 3h-6h; The above dehydrogenation reaction temperature is 160℃~210℃; the liquid mass space velocity of 1,4-pentanediol is 0.05h -1 ~0.25h -1 .

9. Use of the catalyst for preparing γ-valerolactone by dehydrogenation of 1,4-pentanediol as claimed in claim 1 in the reaction of preparing γ-valerolactone by dehydrogenation of 1,4-pentanediol.

10. A method for preparing a catalyst for preparing γ-valerolactone by dehydrogenation of 1,4-pentanediol, characterized in that: The preparation method is any one of Schemes 1 to 7; Solution 1 Weigh 11.33g Cu(NO3)2·3H2O, 96.6g Zn(NO3)2·6H2O and 7.12g Pr(NO3)3·6H2O respectively and dissolve them in a mixed solution of deionized water and DMF with a volume ratio of 0.3:1 to prepare a 1L solution with a metal Cu mass concentration of 3.00g / L, a metal Zn mass concentration of 19.50g / L and a metal Pr mass concentration of 2.31g / L. The Cu / PrO mixed solution was ultrasonically dissolved; after uniform dissolution, 20g triethanolamine complexing agent and 8g SUAEIHDI structure directing agent were added in sequence, and then ultrasonically dissolved for 0.5h. After complete dissolution, the suspension was stirred in a water bath at 80°C for 1h to obtain a uniformly mixed suspension; the uniformly mixed suspension was then transferred to a 100ml high-pressure hydrothermal autoclave, aged at 110°C for 24h, and after cooling, the precipitate was centrifugally washed 3 to 5 times with deionized water and DMF, dried in a drying oven at 100°C for 10h, and then calcined in a muffle furnace at 500°C for 3h to obtain a composite metal oxide catalyst. x -ZnO is catalyst No. 1; Solution 2 16.99g Cu(NO3)2·3H2O, 85.07g Zn(NO3)2·6H2O and 13.46g Pr(NO3)3·6H2O were weighed and dissolved in a mixed solution of deionized water and ethanol with a volume ratio of 0.3:1 to prepare a 1L metal salt mixed solution with a metal Cu mass concentration of 4.50g / L, a metal Zn mass concentration of 17.16g / L and a metal Pr mass concentration of 4.35g / L, and ultrasonically dissolved; after uniform dissolution, 15g triethanolamine complexing agent and 8g SHAEIHDI structure directing agent, and then ultrasonically dissolved for 0.5h. After complete dissolution, stir in a water bath at 80℃ for 1h to obtain a uniformly mixed suspension; then transfer the uniformly mixed suspension to a 100ml high-pressure hydrothermal autoclave and age at 100℃ for 36h. After cooling, the precipitate is centrifugally washed 3 to 5 times with deionized water and ethanol, dried in a drying oven at 120℃ for 10h, and then calcined in a muffle furnace at 500℃ for 5h to obtain a composite metal oxide catalyst. The obtained Cu / PrO x -ZnO is catalyst No. 2; Option 3 14.29g CuCl2·H2O, 32.32g ZnCl2 and 10.96g PrCl3·7H2O were weighed and dissolved in a mixed solution of deionized water and DMF with a volume ratio of 0.3:1 to prepare a 1L Cu salt mixed solution with a metal Cu mass concentration of 6.00g / L, a metal Zn mass concentration of 15.41g / L and a metal Pr mass concentration of 4.14g / L, and ultrasonically dissolved; after uniform dissolution, 15g triethanolamine complexing agent and 10g SUAEIHDI structure directing agent, and then ultrasonically dissolved for 0.5h. After complete dissolution, stir in a water bath at 80℃ for 1h to obtain a uniformly mixed suspension; then transfer the uniformly mixed suspension to a 100ml high-pressure hydrothermal autoclave and age at 120℃ for 30h. After cooling, the precipitate is centrifugally washed 3 to 5 times with deionized water and DMF, dried in a drying oven at 90℃ for 12h, and then calcined in a muffle furnace at 500℃ for 4h to obtain a composite metal oxide catalyst. The obtained Cu / PrO x -ZnO is catalyst No. 3; Option 4 22.65g Cu(NO3)2·3H2O, 90.64g Zn(NO3)2·6H2O and 3.16g Pr(NO3)3·6H2O were weighed and dissolved in a mixed solution of deionized water and ethanol with a volume ratio of 0.5:1 to prepare a 1L Cu salt mixed solution with a metal Cu mass concentration of 6.00g / L, a metal Zn mass concentration of 18.30g / L and a metal Pr mass concentration of 1.02g / L, and ultrasonically dissolved them; after uniform dissolution, 20g triethanolamine complexing agent and 10g SUAEIHDI structure directing agent, and then ultrasonically dissolved for 0.5h. After complete dissolution, stir in a water bath at 80℃ for 1h to obtain a uniformly mixed suspension; then transfer the uniformly mixed suspension to a 100ml high-pressure hydrothermal autoclave and age at 110℃ for 36h. After cooling, the precipitate is centrifugally washed 3 to 5 times with deionized water and DMF, dried in a drying oven at 100℃ for 12h, and then calcined in a muffle furnace at 400℃ for 5h to obtain a composite metal oxide catalyst. The obtained Cu / PrO x -ZnO is catalyst No. 4; Option 5 22.65g Cu(NO3)2·3H2O, 76.31g Zn(NO3)2·6H2O and 12.66g Pr(NO3)3·6H2O were weighed and dissolved in a mixed solution of deionized water and ethanol with a volume ratio of 0.3:1 to prepare a 1L Cu salt mixed solution with a metal Cu mass concentration of 6.00g / L, a metal Zn mass concentration of 15.41g / L and a metal Pr mass concentration of 4.14g / L, and ultrasonically dissolved; after uniform dissolution, 20g triethanolamine complexing agent and 12g SHAEIHDI structure directing agent, and then ultrasonically dissolved for 0.5h. After complete dissolution, stir in a water bath at 80℃ for 1h to obtain a uniformly mixed suspension; then transfer the uniformly mixed suspension to a 100ml high-pressure hydrothermal autoclave and age at 120℃ for 30h. After cooling, the precipitate is centrifugally washed 3 to 5 times with deionized water and DMF, dried in a drying oven at 100℃ for 10h, and then calcined in a muffle furnace at 500℃ for 4h to obtain a composite metal oxide catalyst. The obtained Cu / PrO x -ZnO is catalyst No. 5; Option 6 Weigh 11.33g Cu(NO3)2·3H2O, 85.87g Zn(NO3)2·6H2O and 14.24g Pr(NO3)3·6H2O respectively and dissolve them in a mixed solution of deionized water and ethanol with a volume ratio of 0.5:1 to prepare a 1L solution with a metal Cu mass concentration of 3.00g / L, a metal Zn mass concentration of 17.33g / L and a metal Pr mass concentration of 4.60g / L. The Cu / PrO mixed solution was ultrasonically dissolved; after uniform dissolution, 20g triethanolamine complexing agent and 8g SUAEIHDI structure directing agent were added in sequence, and then ultrasonically dissolved for 0.5h. After complete dissolution, the suspension was stirred in a water bath at 80°C for 1h to obtain a uniformly mixed suspension; the uniformly mixed suspension was then transferred to a 100ml high-pressure hydrothermal autoclave, aged at 110°C for 24h, and after cooling, the precipitate was centrifugally washed 3 to 5 times with deionized water and DMF, dried in a drying oven at 80°C for 10h, and then calcined in a muffle furnace at 500°C for 3h to obtain a composite metal oxide catalyst. x -ZnO is catalyst No. 6; Option 7 22.65g Cu(NO3)2·3H2O, 81.10g Zn(NO3)2·6H2O and 9.49g Pr(NO3)3·6H2O were weighed and dissolved in a mixed solution of deionized water and DMF with a volume ratio of 0.5:1 to prepare a 1L Cu salt mixed solution with a metal Cu mass concentration of 6.00g / L, a metal Zn mass concentration of 16.28g / L and a metal Pr mass concentration of 3.06g / L, and ultrasonically dissolved; after uniform dissolution, 18g triethanolamine complexing agent and 10g SUAEIHDI structure directing agent, and then ultrasonically dissolved for 0.5h. After complete dissolution, stir in a water bath at 80℃ for 1h to obtain a uniformly mixed suspension; then transfer the uniformly mixed suspension to a 100ml high-pressure hydrothermal autoclave and age at 100℃ for 36h. After cooling, the precipitate is centrifugally washed 3 to 5 times with deionized water and ethanol, dried in a drying oven at 110℃ for 10h, and then calcined in a muffle furnace at 500℃ for 5h to obtain a composite metal oxide catalyst. The obtained Cu / PrO x -ZnO is catalyst No. 7.

Citation Information

Patent Citations

  • Cu-based catalyst and method for preparing gamma-valerolactone and delta-cyclovalerolactone by using same

    CN112517013A

  • Method for preparing lactone by liquid-phase dehydrogenation of diol

    CN118772102A

  • Preparing catalyzer of Gamma-butyrolactone through dehydrogenating 1,4 butanediol

    CN1562473A

  • PROCESS FOR PREPARING OF γ-BUTYROLACTONE AND N-METHYL PYRROLIDONE FROM 1,4-BUTANEDIOL

    KR1020110037895A